Comparison of Video-Based Learning Versus Presentations in Lectures Amongst Medical Students in Pharmacology - Pradnya Deolekar; Kavitha Dongerkery; Azra Naseem; Mayakalyani Srivathsan; Sonal Signapurkar; Pramila Yadav; Shloka Hegde; Prasad Kakde (Indonesia Approach Education, 2023)
Innovative teaching methods are constantly being explored to keep students engaged and challenge them academically. This study compared the benefits of video-based learning methods compared to conventional PowerPoint presentations. A total of 150 second-year medical undergraduate students were divided into two groups. Both groups were given a pre-test to test their baseline knowledge of the topic. One group was taught the mechanisms of action of the drugs by using lectures during presentations and the other group was taught with the help of videos. A post-test was conducted, and the scores of the two groups were compared. Feedback questionnaires were also administered to understand the students’ perception of the two teaching methods. The mean score in the video-based group was 15.59+2.46 and, in the presentation group, was 11.43+1.53, out of a total score of 20. A majority of 77.33% preferred video-based learning techniques. This study shows that conventional teaching techniques no longer suffice to keep students engaged and that novel approaches yield higher scores and a better learning experience. Similar studies exploring newer approaches in education are scarce. The findings of this study can be a jumping-off point for inculcating more creative teaching methods in the classroom.